PENERAPAN MODEL POLYA BERORIENTASI MASALAH SOAL CERITA KONTEKSTUAL UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS V SD NEGERI 7 BUGBUG - Putu Suarniti Noviantari (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2018)
This research aimed at (1) improving the fifth grade students’ math problem solving skill in SD Negeri 7 Bugbug in academic year 2017/2018 and (2) investigating the students’ attitude towards mathematics after the teaching learning process applied.This resarch is a clasroom action research consisted of 3 cycles. Each cycle involved plan, action, observation/evaluation, and reflection stages. The subject of the study was the fifth grade students in SD Negeri 7 Bugbug in academic year 2017/2018 with 39 number of students. The data about the students’ math problem solving skill were collected by administering essay test and the data about the students’ attitude were gathered by using questionnaire. The data were anaylzed by means of descriptive analysis. The research findings showed that there was an improvement on the students’ math problem solving skill through the application of Polya Model orienting Contextual Story question problem. The skill of math problem solving was increased 36.07 poin. The students’ attitude towards mathematics after implementing Polya Model orienting Contextual Story question problem was categorized positive with the average score was 38.17.